Morphotectonic and structural signatures of the Savrun Fault: implications for its Neogene evolution (SE Turkey - Akinci, Ahmet Can; Ünlügenç, Ulvi Can; Güneyli, Hakan; Altunel, Erhan; Öçgün, Ali Gökhan; Adliğ, İbrahim (Acta Geologica Polonica, 2026)
The destructive earthquakes of February 6, 2023 in southern Turkey renewed scientific interest in neighboring fault systems whose late-stage tectonic histories remain poorly constrained. One such structure is the Savrun Fault, located northeast of Adana and southwest of the Sürgü-Çardak Fault. This study investigates the tectonic character and Neogene to Quaternary evolution of the Savrun Fault through an integrated approach that combines field observations, lithostratigraphic relationships, morphotectonic indices and GIS-based remote-sensing analyses. The fault extends from Kozan toward Göksun and exhibits well-developed structural elements, including fault planes, fracture systems and associated deformation within Lower to Middle Miocene sedimentary units. In contrast, overlying Quaternary colluvial and alluvial deposits show no evidence of displacement or disruption. Morphotectonic indices (Smf, SL, HI, Af, Vf) reveal localized landscape modification, yet the undisturbed nature of young fluvial and alluvial units indicates that the fault has not experienced documented reactivation during the Quaternary. Despite its close spatial relationship to the seismically active Sürgü-Çardak Fault, the Savrun Fault lacks geomorphic or stratigraphic indicators of late-stage slip. Its southern segment, particularly near the Bağdaş Plateau, is interpreted as a transpressional zone that likely ceased motion during the Middle to Late Miocene. These combined observations suggest that, although structurally prominent, the Savrun Fault plays no measurable role in present-day deformation. The refined tectonic interpretation presented here contributes to a clearer understanding of fault architecture and Neogene landscape evolution in the central Amanos-Göksun region.